AN INVESTIGATION ON TRIPLE HELIX MODEL AND NATIONAL INNOVATION SYSTEMS: THE CASE OF MALAYSIA - Munshi Naser Ibne Afzal; Rini Suryati Sulong; Susmita Dutta; Kasim Mansur (Asian Journal of Innovation and Entrepreneurship, 2018)
The Triple Helix (TH) model (University-Industry-Government relationship) enables numerous nations to enhance and accelerate their development forms. Ventures and universities are customary wellsprings of information. In most creating nations like Malaysia, which is experiencing significant change towards innovation-based economies, the Triple Helix model coupled with the National Innovation System can speed up this progress. This paper investigates the application of the Triple Helix (TH) model inside the National Innovation System in Malaysia. It looks at the degree or level of cooperation amongst organizations and universities in advancing economic development. This research applies mix method in which an integrative investigation of the literature, secondary information and a survey of six Malaysian public universities. The outcomes demonstrate that, the application of Triple Helix model in Malaysian public universities is acceptable. The National University of Malaysia (UKM) performed poorly while University Putra Malaysia (UPM) appears better than others. The outcomes show the need of taking care of distinguished issues in parallel with the execution of the open development idea to extend University-Industry-Government collaboration.